Delayed Post-Hypoxic Leukoencephalopathy Following Nitrite Poisoning: A Case Report and Review of the Literature - Chen, Yankun; Liu, Qiumei; Wang, Jian; Li, Hui; Zhang, Yousheng; Sun, Lingling; Liu, Jianli (Frontiers in Neurology, 2022)
Background:Delayed post-hypoxic leukoencephalopathy (DPHL) is a demyelinating syndrome that occurs days to weeks after the brain has recovered from a coma and is caused by the period of hypoxia.It is characterized by mental disorders,extrapyramidal system symptoms,and motor changes.Common causes include the cardiogenic shock,severe anemia,massive blood loss,and poisoning.Poisoning has been reported to be a cause of DPHL mostly resulting from intoxication with carbon monoxide and several narcotic drugs.There are only a few reports in the literature of DPHL caused by nitrite poisoning.We report DPHL in a patient following nitrite poisoning and a review of the literature n this context. Case presentation:A 64-year-old man presented with dizziness,nausea without vomiting,and later went into a coma after consuming a spare rib soup.After blood gas analysis,we suspected nitrite poisoning combined with metabolic acidosis,hypoxemia,and electrolyte imbalance.He gradually showed neurologic recovery to premorbid baseline after intravenous administration of methylene blue (40 mg) and symptomatic treatment.Two months later, the patient's cerebral magnetic resonance imaging (MRI) showed signs that are compatible with injury,with the patient in late stages of mental decline. Conclusion:Nitrite poisoning can cause DPHL.There is a period of intermittent recovery between the time of poisoning and the development of DPHL,but the specific pathogenesis and treatment are still unclear.